Response control of shear building model for ground motions using tuned mass damper and track nonlinear energy sink - an experimental study - Cherian, Ciby Jacob; Pillai, T.M. Madhavan; Sajith, A.S. (Journal of Structural Engineering, 2024)
This paper presents the results of experimental studies conducted on a small-scale model of a shear building subjected to ground motions. Performance of a Tuned Mass Damper (TMD) as a linear Dynamic Vibration Absorber (DVA) and a track Nonlinear Energy Sink (NES) as a nonlinear DVA are compared considering their effectiveness when employed in this model. Experimentation is carried out in a uniaxial shake table for 32 different earthquake ground motion time histories. The results show that the track NES has a versatile nature in response control and is inherently stable, whereas the TMD in the presented form lacks versatility and has stability issues. As far as the reverse flow of energy from the DVA to the primary structure is concerned, track NES showed better performance. The study also reveals that TMD has a high potential as a vibration control device to reduce the maximum response.